Maternal IntS11 primes embryonic totipotency by organizing early zygotic transcription initiation - Liangliang Wang; Yiru Wang; Yaqi Miao; Yuan Song; Jialiang Zhou; Yuanxiang Zhu; Ying Cheng; Wenxin Zhang; Qinmiao Sun; Fan Lai; Guoqiang Zhang; Dahua Chen (Proceedings of the National Academy of Sciences, 2026)
Zygotic genome activation (ZGA) marks the first transcriptional milestone and establishes embryonic totipotency. Although pioneer factors have been reported to initiate this process, how chromatin is primed for the totipotent state, allowing the binding of pioneer factors for successful ZGA, remains unclear. Here, we identify IntS11, the catalytic subunit of the Integrator complex, as a totipotent determinant of embryonic chromatin governing ZGA in Drosophila . We show that IntS11 functions upstream of pioneer factors in early embryos: Maternal IntS11 depletion substantially impairs RNA polymerase II (Pol II) recruitment, thereby preventing pioneer factors Zelda and GAGA factor (GAF) from accessing regulatory elements and initiating genome-wide zygotic transcription. Mechanistically, IntS11 exerts dual roles: its canonical endonuclease activity is required to sustain major-wave zygotic transcription, while a distinct enzyme-independent function drives de novo Pol II loading and pioneer factor engagement. These findings uncover a fundamental maternal-specific mechanism whereby IntS11 establishes transcriptional competence, ensuring totipotent chromatin states and successful ZGA.